Analisis Jumlah Penumpang dan Penentuan Lokasi Pada Halte Trans Metro Deli Koridor V Berbasis Metode Set Covering Problem - Harahap, Azdi Rihadi; Sutrisno, Sutrisno; Silviana, Nukhe Andri (Jurnal Ilmiah Teknik Mesin & Industri (JITMI), 2024)
The Medan City Government uses the Trans Metro Deli Bus as a mode of transportation in Medan City. The Trans Metro Deli Bus use aims to serve the needs of passengers along the route. For the operation of Trans Metro Deli, it is necessary to have supporting facilities, which is a bus stop. The construction of inefficient bus stops will result in increased transportation problems because many people who should be the target users are lazy to use this mode because of difficulties when using existing facilities. The purposes of the study were to determine the number and location of bus stops and to analyze the number of passengers getting on and off in corridor V. The study was conducted along Corridor V, namely Tembung – Lapangan Merdeka. The research used the Set Covering Problem method to determine the location of an efficient bus stop by minimizing the number of bus stops while being able to meet all demand points. The types of research were survey field research, questionnaire distribution, and direct observation. The data processing results concluded that 12 efficient shelter locations could meet the demand points for the bus stop construction. The bus stops locations that would be built were in the Tembung gas station, Alfamidi Letda Sujono, Budisatrya School, CV. Fajarindo Anugerah Sukses Sejati, Serdang Intersection, Coco H. M. Yamin gas station, the Health Service, Regional Post Office 1, Indosat Office, Indola Mobil, Al-Hidayah School, and Padang Street Intersection and the number of passengers in Corridor V were 2,155 passengers within a month. This study also analyzed the location determination of bus stop when the government had a limited budget for bus stop construction.